Association between atherogenic index of plasma and depression in premenopausal and postmenopausal women: A cross-sectional study - Siyi Deng; Weihong Huang; Jinwen Liao; Yanling Liu; Yang Song; Gang Fu; Mingguo Xu (PLoS ONE, 2025)
Aim This study is the first to investigate the association between the Atherogenic Index of Plasma (AIP) and depression in women, stratified by menopausal status. Methods A total of 9,060 subjects were enrolled from the National Health and Nutrition Examination Survey (NHANES) conducted from 2005 to 2020. AIP was computed by Log10 (triglycerides/high-density lipoprotein cholesterol). Depression was assessed using the Patient Health Questionnaire (PHQ-9), with a score of ≥10 indicating a diagnosis of depression. Multivariate logistic regression, restricted cubic splines (RCS), and subgroup analysis were employed to explore the associations between AIP and depression. Results In comparison to quartile 1, Multivariate logistic regression revealed that AIP in quartiles 2–4 yielded odd ratios (ORs) (95% confidence interval, 95% CI) of premenopausal women of 1.14 (0.87, 1.50), 1.06 (0.79, 1.42), and 1.49 (1.11, 2.00), and postmenopausal women of 0.88 (0.64, 1.22), 1.03 (0.76, 1.41) and 1.40 (1.04, 1.89), respectively. RCS showed a linear correlation between AIP and depression in premenopausal women and a nonlinear correlation between AIP and depression in postmenopausal women. When AIP > 0.60, premenopausal women had an increased risk of depression, while postmenopausal women had a decreased risk of depression. Conclusions This study demonstrates that elevated AIP levels are significantly associated with an increased risk of depression in both premenopausal and postmenopausal women. However, the strength and direction of these associations varied between the two groups, suggesting that menopausal status may play a critical role in modulating the impact of lipid metabolism on mental health outcomes.